An Analysis of the Impact of Covid-19 on Tourism Development and Economy (Case Study in Gili Trawangan, North Lombok NTB) - Wulandari, Yayang Erry; ALqifari, Maruf (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The existence of a pandemic that occurs throughout the world. Policy, Impact, Tourism has an impact on economic activity globally. Especially in the economic and tourism sectors which occur in Gili Trawangan, North Lombok, NTB. NTB tourism, which was previously in the progress stage, has been hampered due to the enormous impact of COVID-19 on the economy and tourism sector. By carrying out supervision and establishing appropriate regulations, the tourism sector in North Lombok Regency, especially in Gili Trawangan, can recover and develop in accordance with the expectations of the tourism economy community. The results of the research that has been carried out are that the COVID-19 pandemic has had a huge impact on the decline in the tourism economy in Gili Trawangan, North Lombok, NTB and it takes quite a long time to recover it again.